2016
DOI: 10.1128/jvi.03204-15
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Tracking Shows that a Point Mutation in the Carnivore Parvovirus Capsid Switches Binding between Host-Specific Transferrin Receptors

Abstract: bDetermining how viruses infect new hosts via receptor-binding mechanisms is important for understanding virus emergence. We studied the binding kinetics of canine parvovirus (CPV) variants isolated from raccoons-a newly recognized CPV host-to different carnivore transferrin receptors (TfRs) using single-particle tracking. Our data suggest that CPV may utilize adhesion-strengthening mechanisms during TfR binding and that a single mutation in the viral capsid at VP2 position 300 can profoundly alter receptor bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Because the dissociation curves here did not fit the basic 1:1 binding model, we used the adhesion-strengthening model (43,57). This model assumes that the binding force can change with contact time, perhaps due to bindingtriggered conformational changes of the capsid (43). However, the initial adhesionstrengthening model applies only to studies where contact times for each capsid particle can be measured, whereas here, we measured the collective loss of many capsids from the surface over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the dissociation curves here did not fit the basic 1:1 binding model, we used the adhesion-strengthening model (43,57). This model assumes that the binding force can change with contact time, perhaps due to bindingtriggered conformational changes of the capsid (43). However, the initial adhesionstrengthening model applies only to studies where contact times for each capsid particle can be measured, whereas here, we measured the collective loss of many capsids from the surface over time.…”
Section: Resultsmentioning
confidence: 99%
“…Characterizing the dissociation curves can also be useful for determining if adhesion-strengthening mechanisms are present, as demonstrated by related work on tracking contact times between individual parvoviruses and TfRs (43). Because the dissociation curves here did not fit the basic 1:1 binding model, we used the adhesion-strengthening model (43,57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies can reveal changes in binding behavior that promote viral attachment. For example, both influenza and canine parvovirus undergo "adhesion-strengthening" where the longer a virion is bound, the more strongly it adheres to the bilayer [37,85]. Overall, these platforms are convenient for gathering insight on this critical virus entry step and how it depends on the host cell surface.…”
Section: Single Virion Tracking Of Bindingmentioning
confidence: 99%
“…The importance of studying the binding step is that the tropism of a virus is strongly tied to its ability to bind various receptors. A nice example, illustrating the power of combining single virion binding measurements with cell infectivity studies, clearly showed that a single mutation in the canine parvovirus capsid is able to alter binding to dog and raccoon transferrin receptors and completely change the tropism of the virus [85].…”
Section: Single Virion Tracking Of Bindingmentioning
confidence: 99%